Evaluation use and decision-making in society : a tribute to Marvin C. Alkin - Christie, Christina A.; Vo, Anne T.; Alkin, Marvin C. (Evaluation and society., 2015)
This volume addresses a fundamental and highly debated issue in the evaluation field - the use of evaluation information for decision-making. Chapter authors honor the contributions of Professor Marvin C. Alkin to the evaluation use literature and advance our thinking on the topic by exploring a wide range of issues related to the theoretical and practical challenges of using evaluation information to make informed, evidence-based decisions. Readers will come away from this volume with a new and clearer understanding of the theoretical, contextual, methodological, and political dimensions of use and with direction for practice. Chapters are written by leading evaluation scholars, including Ernest House; Stewart Donaldson and Tarek Azzam; Eric Barela; Richard D. Nunneley, Jr., Jean A. King, Kelli Johnson, and Laura Pejsa; Eleanor Chelimsky; Michael Quinn Patton; and Wanda D. Casillas, Rodney K. Hopson and Ricardo L. Gomez.Evaluation Use and Decision-Making in Society: A Tribute to Marvin C. Alkin will be of great interest to evaluation students, scholars and practitioners. This volume has scholarly application for those who desire a state-of-the-art resource for the latest insights and perspectives on one of the most pressing issues that the evaluation field faces today, while also serving as a useful guide for both novice and experienced evaluation practitioners. It is appropriate for use in a variety of evaluation courses including Introduction to Evaluation and Procedural Issues in Evaluation as well as topical seminars such as Evaluation Use and Decision-Making.